Analisis Non Performing Loan pada PT Bank BRI tbk - Yuniar, Devina Zahra; Suherman, Enjang; Epty, Dwi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine, analyze, and explain how big the Non Performing Loan (NPL) at Bank BRI Tbk.. This research is a descriptive research, namely research conducted to determine the value of independent variables, either one or more variables without making comparisons or connecting one variable to another. This study uses secondary data from the financial statements of Bank BRI Tbk. taken from the Indonesia Stock Exchange from 2012 to 2021. The technique used in this research is purposive sampling technique. The data analysis technique uses financial analysis and descriptive analysis using the IBM SPSS Statistics 26 analysis tool with the results of this study that Non Performing Loan (NPL) at Bank BRI with an average of 2.19 means Non Performing Loan (NPL) Bank BRI Tbk. below the standard criteria set 5% can be said to be good.